INTEGRATION AND DIGITALIZATION AS MODERN EDUCATIONAL TRENDS - KONDUR, Oksana; TSIUNIAK, Oksana; VERBESCHUK, Svetlana (Mountain School of Ukrainian Carpaty, 2024)
The article examines the relevance of the integration approach and digitalization in education, in particular their significance for primary school. It is emphasized that integration contributes to the formation of interdisciplinary connections, the development of critical thinking, creativity and a holistic understanding of the world. The use of an integration approach allows building a holistic understanding of the material, increasing children's motivation to learn. The role of digitalization in the implementation of an integration approach is highlighted, which provides new opportunities for teaching students and improving the educational process. Digital tools contribute to the creation of adaptive learning that takes into account the individual characteristics of students. Modern digital tools that effectively support interdisciplinary learning are described. Examples of their use for creating integrated lessons and projects are given. The emphasis is placed on the need to prepare future teachers for the implementation of integration learning using digital technologies, which includes pedagogical practice and the development of professional digital competencies. A trained teacher is able to introduce these elements into the educational process, ensuring its compliance with modern requirements. A teacher who is proficient in digital technologies and integration techniques helps students not only acquire knowledge, but also develop critical thinking, creativity, communication skills, and digital literacy.